2003
DOI: 10.1183/09031936.03.00010303
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised self-testing of airway obstruction by forced oscillation at the patient's home

Abstract: As active patient cooperation is not required, the forced oscillation technique (FOT) could be suitable for measuring airway obstruction in routine home applications. Nevertheless, FOT has never been used at the patient9s home to date. The aim of this study was to assess the feasibility of FOT and the reproducibility of measured respiratory resistance (Rrs) in routine patient self-testing at home.Altogether, nine asthmatic patients self-measured their Rrs with a portable FOT device and spirometry for 10-14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
1
13
0
2
Order By: Relevance
“…(5-15%) [19,20,26], and similar to those reported for plethysmographic measurements [9,27]. Among anthropometric variables analysed, height was the best predictor for Rrs and FN, and contribution of age and weight was either nonsignificant or negligible.…”
Section: Respiratory Resistance In the Elderly Yf Guo Et Alsupporting
confidence: 66%
“…(5-15%) [19,20,26], and similar to those reported for plethysmographic measurements [9,27]. Among anthropometric variables analysed, height was the best predictor for Rrs and FN, and contribution of age and weight was either nonsignificant or negligible.…”
Section: Respiratory Resistance In the Elderly Yf Guo Et Alsupporting
confidence: 66%
“…Thus reliable measurements of impedance during quiescent breathing, especially using a portable home FOT device with telemedicine capabilities 245859 , may be useful for monitoring the dynamics of airway obstruction and its evolution over periods of weeks or months. Such data could provide far more insight into the management and control of obstructive lung diseases when compared to traditional, intermittent clinical assessment 151 .…”
Section: Discussionmentioning
confidence: 99%
“…Rigau et al have shown that FOT was potentially applicable to home monitoring 5859 . A recent study by Dellaca et al demonstrated the feasibility of using an inexpensive FOT system for real-time data acquisition, processing, and internet streaming 24 .…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…The Forced Oscillation Technique (FOT) measures the mechanical properties of the lung during tidal breathing in a way that is simple to perform without supervision or effort, is operator independent and can be undertaken at home by COPD patients 18,19 . FOT can also detect changes in lung mechanics acutely after a bronchodilator 20 and during recovery from an exacerbation [21][22][23] , making it a potentially attractive way to objectively define exacerbation events in a telemonitoring programme.…”
Section: Introductionmentioning
confidence: 99%